Faktor-faktor yang Mempengaruhi Perilaku Perpindahan Merek pada Konsumen (Studi Kasus pada Produk IndiHome di Wilayah Bandung Raya) - Hijriany, Rahma Wulan; Purwaningsih, Siti Samsiyah (Ebiz Prima Nusa, 2022)
The rapid development of technology aligns with the development of the internet, which keeps growing on a daily bases, resulting in the proliferation of internet service providers today. This is due to the high public demand for internet access, which has turned it into a